Environment and Some Aspects of Religious Education - E., Nadirova G. (Farabi Journal of Social Sciences, 2019)
Abstract. The religious situation and religious beliefs in Kazakhstan are a dynamic, constantly changing phenomenon. They are reflected in numerous processes and actions, that we can observe every day and that require our study and reflection. Islam in Kazakhstan is able to interact with the new realities and «challenges», and create new meanings and correct personal and social beliefs. Religious education can contribute to the solution of today’s social problems, such as environmental, act as a stimulus for the development of environmental awareness. Scientists and environmental activists all over the world have begun to develop educational strategies to revive the environmental teachings and practices of Islam. They participate in the formation of eco-ethics of Islam and the development of teaching materials for the introduction of eco-ethics in a rich educational environment of the Muslim world.